Co-prescribing of antidepressants and opioids for non-cancer pain in England, 2010–2019: a descriptive study using CPRD primary care electronic health records - Jake Butler; Rebecca M. Joseph; Carol Coupland; Roger David Knaggs; Anthony J. Avery; Richard Morriss; Debbie Butler; Louisa Gerrard; Dave Waldram; Ruth H. Jack (BMC Primary Care)
Abstract Background There is a complex relationship between pain and mood disorders, and interactions between opioids and antidepressants can affect the effectiveness and adverse effects of these medicines when taken together. However, little is known about the scale of co-prescription for these medicines. Methods We used routinely collected primary care data from the Clinical Practice Research Datalink to describe the extent of opioid and antidepressant co-prescribing in over 4.3 million adults in England. Linked data included deprivation information and hospital episode statistics admitted patient care data to improve completeness of ethnicity information. We identified all primary care prescriptions of opioids and antidepressants between 2010 and 2019 and counted if an opioid and antidepressant prescription overlapped, and if so, for how long. People were censored at the first date of a record of cancer, terminal illness, heart failure or opioid misuse. Results There were 4,355,694 people included in the study population. Of these, 304,029 (7.0%) had an opioid and antidepressant co-prescribed at least once during the study period. The prevalence of co-prescribing increased from 35.8 per 1000 person-years in 2010 to 44.1 in 2015 and then decreased to 39.2 in 2019. Co-prescribing rates were higher in females, older age groups, people living in more deprived areas and the White ethnic group. The overall median length of the opioid and antidepressant co-prescriptions was 29 days (interquartile range: 17 to 51 days). The most commonly co-prescribed medicines were codeine and amitriptyline, co-prescribed 235,017 times to 87,274 people. The second most commonly co-prescribed combination was codeine and citalopram, co-prescribed 55,792 times to 158,812 people. Combinations of opioids and antidepressants both metabolised by CYP2D6 were also common. Conclusions There is a substantial group of people co-prescribed opioids and antidepressants in England, including combinations that may be less effective. This information will be useful to help GPs, dispensing professionals, policymakers and others understand how many people in the UK may be at risk of harm from using both types of medicines at the same time, and which groups are particularly affected. Future research should determine whether there are higher risks of adverse events in these co-prescribed groups.